Holoseum: An Educational Platform for the Development of Ethnographic Museums of Death Through the Integration of Sustainable Immersive Technology - Rani Rakhmawati (Biokultur, 2026)
The declining interest of the younger generation in Museum Etnografi, as well as the lack of interactive interpretations of death culture, has driven the development of HOLOSEUM as an immersive technology-based educational platform to enhance contextual understanding, emotional engagement, and cultural appreciation. This study aims to develop and test the effectiveness of HOLOSEUM as an immersive technology based educational platform in revitalizing the cultural significance of death in ethnographic museums. The method used is Research and Development (R&D) employing the ADDIE model, which involves expert validation and user testing at the Museum of Death Ethnography, Airlangga University. The results showed a significant increase in cultural understanding (p<0.001) with a high effect size (Cohen’s d= 1.25). Levels of learning interest and cultural appreciation were in the high category (mean = 4.32/5), and the system’s usability was classified as good (SUS = 74.6). Qualitative findings suggest that the immersive experience enhances users’ emotional engagement, although there are limitations in representing spiritual depth. This study concludes that HOLOSEUM is effective as a technology-based cultural learning medium, but requires an ethical and participatory approach in its implementation.